Primer caso centroamericano de coccidioidomicosis - Trejos, A.; Castro, A. (Revista de Biología Tropical, 1953)
1. The first case of coccidioidomycosis in Central America, a patient from Honduras who had been living for the last 24 years in the Comayagua Valley, 15 described. 2. The diagnosis was confirmed by mycological examinations, and additional studies with respect to the morphology of C. immitis during its parasitic phase, were made. 3. The Valley of Comayagua, Honduras, is discussed as a new endemic area for coccidioidomycosis.